Coincidence and conditions: An in-depth case study of a successful age group within a grassroots football club. Issue 3 (4th May 2022) - Rossing, Niels N.; Mogensen, Christian G.; Pedersen, Mathias M.; Martin, Luc J.
Abstract: This case study involved an in-depth exploration of a successful age group within a grassroots football club in Denmark. The research was conducted through observations, informal discussions, semi-structured interviews with parents and coaches, and focus groups with select athletes. Using thematic and dense case study analysis, six themes were generated that varied from being Fortunate Coincidences to Controlled Conditions. The coincidental themes involved the stability of team membership and close physical proximity of members, whereas the conditions included club support? Material help only, coaches as environmental engineers, good players come from good homes, and the power of quality group dynamics and values. Throughout the research process, the research team paid close attention to coincidental features that could have influenced the successful nature of this age group. In considering those coincidental features, it was also important to explore practices undertaken and the roles of the social agents within the age group. This age group was found to demonstrate an inclusive attitude encompassing team unity, respect, and a flat hierarchy . In addition, the coaches promoted a philosophy as early value setters and a development first attitude, which was crucial to the environment described herein. To conclude, although coincidences were acknowledged to be a primary factor in the development and retainment of these youth athletes, this case leveraged the opportunities afforded to them to provide a rich environment for those involved. Lay summary: This study explored a successful age group within a grassroots football club. The age group consisted of both coincidental features and conditions. The age group dynamics were characterized by their respect and team unity across skill level. The case illustrates an emphasis on mass participation and talent development. Implications for practice:  Clubs and coaches ought to be aware of both the coincidental features presented to them within their sport program when attempting to facilitate fertile conditions for those involved.